The Effects Of Micro-Learning On Spanish Language Learners’ Vocabulary Acquisition In A Technical University In Malaysia - Khong, Hou Keat (2023)
This study reports an 11-week mixed-methods quasi-experiment investigating the effect of Micro-Learning (ML) on the acquisition of four vocabulary knowledge (VK) aspects among Malaysian students. Students (N = 67) attending the university Spanish course were divided into three groups: the experimental group received a four-week ML explicit vocabulary instruction, the comparison group received a comparable one-off online explicit vocabulary instruction, and the control group received no treatment. The target language items involved 140 Spanish words and the VK was measured using multicomponent vocabulary tests. These test results were corroborated by qualitative data on the three aspects of ML to provide a deeper understanding of the quantitative results. The findings showed that both ML and one-off explicit vocabulary instructions proved effective in facilitating multicomponent vocabulary acquisition and retention among the Malaysian learners of Spanish, and that ML treatment was superior in the retention of Form and Meaning (d = 0.75), and Associations (d = 1.08). The three aspects of ML (design, affective, and behavioral) were found to affect the Spanish vocabulary acquisition when they worked in tandem as described in the theoretical model.